Children's Exposure to Violence: The Underlying Effect of Posttraumatic Stress Symptoms on Behavior Problems. Issue 1 (7th January 2016) - Yoon, Susan; Steigerwald, Stacey; Holmes, Megan R.; Perzynski, Adam T.
Abstract: In this study we investigated whether witnessing violence and violence victimization were associated with children's internalizing and externalizing behavior problems and examined the mediating role of posttraumatic stress (PTS) symptoms in these relationships. Secondary data analysis was conducted using 3 waves of data from the National Survey of Child and Adolescent Well‐Being. Path analyses were conducted to test direct and indirect effects of violence exposure on behavior problems, using 2, 064 children (ages 8–15 years) reported to Child Protective Services for maltreatment. Being a victim of violence in the home was directly associated with more internalizing (β = .06, p = .007) and externalizing behavior problems (β = .07, p = .002), whereas witnessing violence was not directly related to either internalizing (β = .04, p = .056) or externalizing behavior problems (β = .03, p = .130). PTS symptoms mediated the effects of witnessing violence and violence victimization on internalizing behavior problems (β = .02, p = .002). Our findings suggest that PTS symptoms may be a mechanism underlying the association between violence exposure and internalizing behavior problems ( R 2 = .23), underscoring the potential importance of assessing PTS symptoms and providing targeted trauma‐focused interventions for children exposed to violence at home.